2007
DOI: 10.1177/000313480707300712
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Electrocardiographic Change, Cardiac Troponin Elevation, and Survival after Major Vascular Surgery: A Community Hospital Experience

Abstract: Cardiovascular disease is the leading cause of perioperative morbidity and mortality after vascular surgery. The purpose of this study was to identify risk factors for myocardial ischemia after vascular surgery and to investigate a potential association of ischemia with mortality in a community hospital setting. A retrospective review was conducted after 190 major vascular procedures. Electrocardiogram (ECG) results and troponin I levels were obtained serially during the first 24 postoperative hours. Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(50 reference statements)
0
6
0
1
Order By: Relevance
“…All studies evaluated the prognostic properties of troponin measurement after surgery (14 evaluated mortality, 6 -16,18,22,23 and five evaluated major cardiovascular events 12,14,16,21,22 ), whereas only four studies evaluated the prognostic properties of CK-MB measurement. 6,10,11,18 Ten studies evaluated troponin I exclusively, 8,9,[12][13][14][15][16]18,22,23 three evaluated troponin T exclusively, 7,11,21 and two studies evaluated troponin I and T. 6,10 There was wide variation across studies in the threshold for an increased troponin and the timing and frequency of troponin measurements. An increased troponin measurement was observed in 8.4 -52.9% of patients across studies, and an increased CK-MB was observed in 7.6 -23.7% of patients across studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies evaluated the prognostic properties of troponin measurement after surgery (14 evaluated mortality, 6 -16,18,22,23 and five evaluated major cardiovascular events 12,14,16,21,22 ), whereas only four studies evaluated the prognostic properties of CK-MB measurement. 6,10,11,18 Ten studies evaluated troponin I exclusively, 8,9,[12][13][14][15][16]18,22,23 three evaluated troponin T exclusively, 7,11,21 and two studies evaluated troponin I and T. 6,10 There was wide variation across studies in the threshold for an increased troponin and the timing and frequency of troponin measurements. An increased troponin measurement was observed in 8.4 -52.9% of patients across studies, and an increased CK-MB was observed in 7.6 -23.7% of patients across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these 10 studies performed time-to-event analyses and reported hazard ratios (HRs) from Cox proportional hazards models. 6,7,[11][12][13][14][15][16] One of these studies also performed a logistic regression analysis, but did not report the numerical results. 16 The authors of this study provided us with the ORs from this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PMI is recognized as an important surrogate for shortand long-term mortality after non-cardiac surgery. [1][2][3][4][5][6][7][8][9] The main pathology of PMI is myocardial ischemia, possibly caused by pre-existing CAD, plaque rupture, or imbalance between myocardial oxygen supply and demand. Anemia and hemodynamic instability caused by major bleeding during surgery may accelerate myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in 8-52% of patients who undergo non-cardiac surgery and has received considerable attention since it was reported to be associated with an increased risk of morbidity and mortality. [1][2][3][4][5][6][7][8][9] The main pathology of PMI is thought to be myocardial ischemia, possibly attributable to pre-existing coronary artery disease (CAD), plaque rupture, or imbalance between myocardial oxygen supply and demand. Interestingly, the incidence of coronary artery stenosis is poorly correlated patients undergoing non-cardiac surgery.…”
mentioning
confidence: 99%
“…There are several reasons why percutaneous treatment with out‐patient surveillance is attractive to many patients with lifestyle limiting claudication compared to surgical bypass. These include the less invasive approach and lower cardiovascular risk afforded by percutaneous treatment compared to femoral bypass surgery where rates of perioperative mortality and myocardial infarction are ∼1–3% and 10–15% [6–11]. In contrast, the risks associated with initial and repeat percutaneous treatment are much lower than initial and repeat vascular surgeries.…”
Section: Discussionmentioning
confidence: 99%